Good quality end-of life care for people with an intellectual disability: A critical interpretive synthesis protocol. - Margaret Haigh; Mary McCarron; Philip McCallion; Pavithra Pavithra; Martin McMahon (PLoS ONE, 2024)
People with an intellectual disability face inequality accessing healthcare that extends to end-of-life care. Furthermore, end-of-life care for people with an intellectual disability is more complex than that for the general population. This protocol sets out how our review will explore the available evidence and identify the key characteristics of care that are required for people with an intellectual disability to have a good end-of-life experience. A critical interpretive synthesis approach will be adopted, combining some elements of a systematic review with interpretive synthesis. This approach has been selected as it allows a diverse body of literature to be considered. Furthermore, it is compatible with theory generation allowing new insights to emerge in an iterative process. Electronic databases and grey literature sources will be searched using pre-defined search terms. Following initial title and abstract screening, eligible papers will undergo full text screening. Papers that are deemed to be 'fatally flawed' will be excluded and remaining papers appraised for relevance. Resultant papers will be included in the sampling frame from which data extraction will occur. An existing framework outlining key factors in the provision of excellent end-of-life care to people with an intellectual disability will be used to support data extraction and synthesis. Data extracted will be integrated into a synthesising argument in the form of a theoretical framework. This will identify the key characteristics in the provision of care that are required for people with an intellectual disability to have a good end-of-life experience. The developing theoretical framework will guide further selection of relevant literature to fill any conceptual gaps until saturation is reached. Our review will add to the existing body of evidence, shedding light on the key factors necessary in the provision of care to ensure that people with an intellectual disability have a good end-of-life experience.